Resposta fisiológica de limas ácidas Tahiti enxertadas em porta-enxertos ananicantes sob diferentes manejos do solo - Padilha, Pedro Henrique Barrio (Universidade Federal de São Carlos, 2024)
Brazilian citriculture plays a significant role both economically and socially, and the introduction of new materials, such as scion and rootstock varieties, has enabled the industry to overcome numerous challenges, aiming for the implementation of more productive crops. This study aimed to evaluate the physiological response and development of Tahiti acid lime plants grafted onto dwarfing rootstocks subjected to conventional and ecological soil management. To achieve this, an experiment was established in 2020 with the objective of assessing different types of management and combinations of scion and rootstocks in the production of Tahiti acid lime. Prior to planting the citrus seedlings, Urochloa ruziziensis was sown in the interrows. The 12-month-old Tahiti acid lime seedlings were planted in seven rows, with a spacing of 6.0 x 2.5 meters. The trial was set up in a randomized block design, in a 2x3x2 factorial scheme, comprising: two types of soil management (1. conventional management using conventional m
Physiological response of Tahiti acid limes grafted on dwarfing rootstocks under different soil management
Keywords: Prolina; Lipoperóxidos; Estresse; Ecológico; Convencional; Proline; Lipoperoxides; Stress; Ecological; Conventional; CIENCIAS AGRARIAS::AGRONOMIA